UPAYA MENINGKATKAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA PESERTA DIDIK KELAS V.A DI SD PALEMBANG - Nurhasanah Nurhasanah (Universitas Negeri Medan, 2022)
The purpose of this study was to improve Civics learning outcomes in class V.A students at SD Negeri 90 Palembang. This study used 2 cycles of action research and before the cycle was carried out pre-cycle data was taken. The research was carried out at SD Negeri 90 Palembang. 25 students. The time of this research was carried out from August 2017 to October 2017, because in this academic year the researcher taught Civics subjects in class V.A SD Negeri 90 Palembang. Each round consists of four stages, namely: design, activity and observation, reflection and revision. From the results of the analysis, it was found that the learning outcomes of students increased from cycle I to cycle II. Mastery learning increased starting from the pre-cycle, cycle I, and cycle II, respectively 24%, 64% and 88%. In the second cycle, students' learning mastery classically has been achieved and has improved very well.